DIFFICULTIES OF DIAGNOSTICS AND CHOICE OF SURGICAL APPROACH IN PATIENTS WITH DUCTAL CHOLANGIOCARCINOMA - D. A. Granov; I. V. Timergalin (Вестник хирургии имени И.И. Грекова)
Diagnostics and treatment of ductal cholangiocarcinoma is an actual and complicated problem of modern hepatopancreatobiliary surgery. The data of preoperative examination using modern methods weren’t always well-defined. This fact didn’t allow clinicians to choose the common treatment strategy and improve the prognosis. The main problem of diagnostic stage was a low morphological verification of the disease, so the diagnosis was confirmed in 17,5% patients. The article presents the results of examination and surgical treatment of 40 patients with suggested diagnosis of ductal cholangiocarcinoma. Indications to operation were based on examination data (CT, MRI, cholangiography, angiography, tumor markers tests) and signs of complications (jaundice, cholangitis, liver abscess). The absence of morphological verification couldn’t be the reason for rejection from the operation. Radical operative intervention had a distinctive advantage. The surgery gave the chance for positive long-term prognosis in case of cancer and allowed doctors to cure patients in case of benign tumor. Functional state of the liver and morphological changes of the removed share should be considered in case of hilus carcinoma. This approach has to be strictly individual and medical care should be applied in special medical centers.